RESEÑA de: D’Almeida, Luís Duarte; Edwards, James y Dolcetti, Andrea (Eds.). Reading HLA Hart’s The Concept of Law. Oxford: Hart Publishing, 2013. 309 págs - Puig Hernández, Marc-Abraham (Revista de Derecho de la UNED (RDUNED), 2016)
-